Measles - a disease that should be a thing of the past, but returns - Głowacka, Katarzyna; Fabian-Danielewska, Anna (Journal of Education, Health and Sport, 2019)
The measles is a viral respiratory disease, in the form of an acute febrile illness with mucous membrane involvement and a rash. Human being is the only reservoir for this pathogen. Measles are highly contagious, spreads through the coughs and sneezes and by direct contact with secretions of an infected person. The risk of developing measles in a non-immune person, is more than 90% after contact with the pathogen. One ill person can infect 12-18 people. Permanent immunity gives the suffering from measles in the past, two doses of the vaccine give a resistance of 97%. Newborns are protected for the first 6-12 months of life with antibodies their get in the womb from mother if she is immune from getting sick. Measles is a mild or moderately severe disease. Complications occur in about 30% of patients. It include: inflammation of the middle ear, pneumonia, brain, myocardium, blindness, and a very rare complication - subacute sclerosing inflammatory brain - progressive CNS neurodegeneration that leads to death a few or a dozen years after the measles eradication. There is no causative treatment in a case of measles. We can only use symptomatic treatment - antipyretic drugs, antitussive, proper hydration and nourishment of the patient, rest, darkening of the room in the case of photophobia. For specific measles prevention methods, we include preventive vaccination and passive immunoprophylaxis. The MMR vaccine is usually well tolerated, rarely gives vaccine adverse events. . Anti-vaccinations movements have been gaining popularity in the world for years, unfortunately contributing to the recurrence of disease epidemics that have nearly been eliminated.